High-speed integrated circuit technology : towards 100 GHz logic - Rodwell, Mark J. W. (Selected topics in electronics and systems, 2001)
This book reviews the state of the art of very high speed digital integrated circuits. Commercial applications are in fibre optic transmission systems operating at 10, 40 and 100 Gb/s, while the military application is ADCs and DACs for microwave radar. The book contains detailed descriptions of the design, fabrication and performance of wideband Si/SiGe-, GaAs-, and InP-based bipolar transistors. The analysis, design and performance of high speed CMOS, silicon bipolar and III-V digital ICs are presented in detail, with emphasis on application in optical fibre transmission and mixed signal ICs. The underlying physics and circuit design of rapid single flux quantum (RSFQ) superconducting logic circuits are reviewed, and there is extensive coverage of recent integrated circuit results in this technology.